Analisis Yuridis Terhadap Mitigasi Risiko Penyaluran DAU/DBH pada HIMBARA - M Rivky Abdillah Putra; Annisa Sativa (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
This normative-juridical study aims to analyze the mechanism for distributing the General Allocation Fund (DAU) and Revenue-Sharing Fund (DBH) through the Association of State-Owned Banks (HIMBARA) to "Merah Putih" Village/Urban Village Cooperatives, in accordance with Minister of Finance Regulation (PMK) Number 15 of 2026. A statutory approach reveals that HIMBARA plays a strategic role in verification, disbursement, and oversight to ensure the effectiveness and accountability of public funds. the findings demonstrate that HIMBARA plays a strategic role in verification, distribution, and monitoring to ensure the effectiveness and accountability of public funds. The implemented risk mitigation scheme encompasses administrative, operational, legal, and moral hazard risks rooted in the prudential principle and Good Corporate Governance (GCG). Normatively, PMK Number 15 of 2026 provides a clear legal foundation for risk mitigation; however, practical challenges remain regarding the precise boundaries of legal liability, potential jurisdictional overlaps, and digital transformation risks in fund disbursement systems.